Analysis of Educational Game Tools for Enhancing Early Childhood Creativity in SIKL - Qorri Anggraini; Kurnia Jayadinata, Asep; Ardiyanti, Dhea; Panji Dermawan, Risang (Lentera Pendidikan : Jurnal Ilmu Tarbiyah dan Keguruan, 2025)
This study examines the use of Educational Game Tools (EGT) to enhance early childhood creativity at Sekolah Indonesia Kuala Lumpur (SIKL), focusing on the availability of EGT, teacher facilitation strategies, and their impact on children’s creative development. The study employed a descriptive qualitative approach, involving two kindergarten teachers and one vice principal of curriculum as participants, with children aged 4–6 years as the subjects of observation. Data were collected through in-depth interviews, participant observation, and document analysis, and were subsequently analyzed using interactive models. The findings indicate that EGT availability is limited, with wooden blocks being the primary material due to space constraints and ongoing building renovations. Teachers employ adaptive facilitation strategies, including observation, the use of open-ended questions, and the integration of EGT within thematic learning. Despite these limitations, children demonstrate notable creativity, including improvements in fluency and flexibility of thinking, as well as enhanced social skills. This study underscores the significance of creative learning strategies, even when resources are limited. Abstrak: Penelitian ini mengkaji penggunaan Alat Permainan Edukatif (Educational Game Tools/EGT) untuk meningkatkan kreativitas anak usia dini di Sekolah Indonesia Kuala Lumpur (SIKL), dengan fokus pada ketersediaan EGT, strategi fasilitasi guru, dan dampaknya terhadap perkembangan kreativitas anak. Penelitian ini menggunakan pendekatan deskriptif kualitatif, dengan melibatkan dua guru taman kanak-kanak dan satu wakil kepala sekolah bidang kurikulum sebagai partisipan, serta anak-anak berusia 4–6 tahun sebagai subjek observasi. Data dikumpulkan melalui wawancara mendalam, observasi partisipatif, dan analisis dokumen, kemudian dianalisis menggunakan model interaktif. Temuan penelitian menunjukkan bahwa ketersediaan EGT terbatas, dengan balok kayu sebagai bahan utama karena keterbatasan ruang dan renovasi bangunan yang sedang berlangsung. Guru menerapkan strategi fasilitasi adaptif, termasuk observasi, penggunaan pertanyaan terbuka, dan integrasi EGT dalam pembelajaran tematik. Meskipun terbatas, anak-anak menunjukkan kreativitas yang nyata, termasuk perkembangan dalam kelancaran dan fleksibilitas berpikir, serta peningkatan keterampilan sosial. Penelitian ini menekankan pentingnya strategi pembelajaran kreatif, meskipun dengan sumber daya yang terbatas.